Operations Strategies and Change Management - Srinivas Rao, G. (Prabandhan: Indian Journal of Management, 2012)
Managing change is a complex issue and its challenging too. It includes aspects of relationship with customers, maintaining schedules, transforming resources, comfort & affordability, and the strategic leadership. The operation strategy relates to total business in an organization as an implementer, supporter and driver of business. It deals with overall activities, contributes to organizational success, reduces costs and increases productivity. It is the key to stakeholder and customer satisfaction by maintaining quality. Thus, operating strategy is the inevitable component that no company can survive in the long term without successfully designing operational strategies in the global competition.